Visual outcome three and six months after implantation of Acri.LISA 366D lenses - Lubiński, Wojciech; Podborączyńska-Jodko, Karolina; Gronkowska-Serafin, Jolanta; Karczewicz, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Purpose: To evaluate 3 and 6 months binocular visual outcomes after microincision cataract surgery (MICS) with implantation of multifocal, hybrid Acri.LISA 366D IOLs. Material and methods: Three and six months after bilateral MICS with Acri.Lisa 366D implantation, 40 eyes of 20 patients were evaluated for surgical induced astigmatism (SIA – vector analysis), binocular UDVA, UNVA and UIVA (logMAR), spectacle independence, contrast sensitivities (CS-CSV-1000), subjective symptoms, patient satisfaction (Type Questionnaire) and complications. Results: Three and six months after surgery, SIA was equal 0.55 D and 0.58 D subsequently. Three months postoperatively mean binocular UDVA did not differ significantly from the six-month follow-up (-0.10 ± 0.17 versus -0.14 ± 0.11; p = NS). All patients had very good spectacle-free visual function at all distances and were totally spectacle independent. Mesopic distance and photopic distance and near CS were within normal age-matched limits at both follow-ups and did not change during observation time. A low degree of glare/halo was detected in 75% of subjects. Overall patient satisfaction was very high (9.05/10). There were no postoperative complications. Conclusions: Multifocal Acri.LISA 366D IOL implantation in selected cataract patients provides a very good visual outcome, a high level of patient satisfaction and spectacle-free visual function.